2011
DOI: 10.1182/blood-2011-01-328682
|View full text |Cite
|
Sign up to set email alerts
|

Irgm1 protects hematopoietic stem cells by negative regulation of IFN signaling

Abstract: The IFN-inducible immunity-related p47 GTPase Irgm1 has been linked to Crohn disease as well as susceptibility to tuberculosis. Previously we demonstrated that HSC quiescence and function are aberrant in mice lacking Irgm1. To investigate the molecular basis for these defects, we conducted microarray expression profiling of Irgm1-deficient HSCs. Cell-cycle and IFN-response genes are up-regulated in Irgm1(-/-) HSCs, consistent with dysregulated IFN signaling. To test the hypothesis that Irgm1 normally down-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 43 publications
4
75
1
Order By: Relevance
“…It is important to note that the serum cytokine data indicated that IFN-␥ levels were elevated systemically in Irgm1-deficient mice (which is in agreement with a previous analysis of Irgm1-deficient mice (40)). Consequently, it is likely that macrophages in those mice are already primed with IFN-␥, and thus we chose to examine the responses of cultured macrophages primed with IFN-␥.…”
Section: Resultssupporting
confidence: 70%
“…It is important to note that the serum cytokine data indicated that IFN-␥ levels were elevated systemically in Irgm1-deficient mice (which is in agreement with a previous analysis of Irgm1-deficient mice (40)). Consequently, it is likely that macrophages in those mice are already primed with IFN-␥, and thus we chose to examine the responses of cultured macrophages primed with IFN-␥.…”
Section: Resultssupporting
confidence: 70%
“…This inflammatory phenotype and impaired erythropoiesis that develops in mice is consistent with the changes in the aging hematopoietic compartment described as "myeloid skewing". 48,49 We also found that IFNγ, which is known to have deleterious effects on hematopoietic stem cells, 50 increased with age. Though aged mice demonstrated the widest distribution of serum Epo concentrations, Epo was not significantly elevated in the majority of aged mice despite anemia.…”
Section: Discussionmentioning
confidence: 65%
“…3 This follows previous papers demonstrating that IFN-␣ stimulates normal hematopoietic stem cells from dormancy, [4][5][6] which may eventually lead to depletion of the hematopoietic stem cell pool. Whether this differential effect is more pronounced on normal stem cells or on stem cells dysregulated by somatic mutations (such as those in polycythemia vera), where a yet-to-be-defined single or several somatic mutations generate a clone 7,8 which is followed by a clonal evolution marked by JAK2V617F mutation (see figure panel A), remains to be shown.…”
mentioning
confidence: 82%
“…2 This work stems from the notion that in addition to recurrent structural chromosome and gene aberrations, epigenetic changes (those that alter gene transcription without changing DNA sequences) also occur in AML blasts. 3 DNA hypermethylation is one form of reversible epigenetic alteration that occurs through DNA methyltransferases (DNMTs) enzymatically adding a methyl (CH3) group to cytosine in the context of cytosine-guanine (CpG) dinucleotide sequences. In AML, hypermethylation of CpG islands, CpG-rich regions often associated with gene promoters, results in the silencing of tumor suppressor genes and other genes important for hematopoietic differentiation.…”
Section: Epigenetic Priming: the Target? ----------------------------mentioning
confidence: 99%